Optimization of Transient Focal Cerebral Ischemia Model by Middle Cerebral Artery Occlusion - Bahman Jalali Kondori; Mohammad Hossein Asadi; Javad Raouf Sarshouri; Hossein Bahadoran (Negah Institute for Scientific Communication, 2017)
Introduction: Cerebral ischemia is one of the most common causes of death in human populations in the industrial communities. The need for animal models is inevitable to study the pathophysiology and treatment of cerebral ischemia in human. The current study aimed at evaluating the strengths and weaknesses of different techniques used to create ischemia in previous studies and optimizing the transient focal cerebral ischemia model by Middle Cerebral Artery Occlusion (MCAO).  Methods: In the current study, 35 male Wistar rats were divided into 4 groups. The weight of rats in the groups 1 and 2 ranged 250 to 270 g with ischemic induction duration of 60 and 90 minutes, respectively. The weight of rats in the groups 3 and 4 ranged 250 to 310 g with ischemic induction duration of 60 and 90 minutes, respectively. The ischemia was performed by the MCAO method using a special filament. Motor neurological disorders were assessed 24 hours after ischemia. The ischemic area was appeared using Triphenyl-Tetrazolium Chloride (TTC) staining. Histopathological examination of the ischemic area was performed using the Nissl staining.  Results: In a similar duration of ischemia, the ischemic lesion volume was significantly greater in the group with lower weight. The mortality rate was lower in the groups with lower weights compared with other groups.  Conclusion: Based on the results of the present study, it is better to use rats with lower weights to create transient focal cerebral ischemia model using MCAO method.